2022
DOI: 10.3389/fphar.2022.940773
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Tripterygium wilfordii Hook.F.- Trichosanthes kirilowii Maxim decoction in treatment of diabetic kidney disease based on network pharmacology and molecular docking

Abstract: Background: Diabetic kidney disease (DKD) is the most common cause of end-stage renal disease. The effective treatment of DKD would rely on the incorporation of a multi-disciplinary. Studies have shown that Tripterygium wilfordii Hook.F. and Trichosanthes kirilowii Maxim have remarkable curative effects in treating DKD, but their combination mechanism has not been fully elucidated.Methods: We explored the mechanism of Tripterygium wilfordii Hook.F.-Trichosanthes kirilowii Maxim decoction (Leigongteng-Tianhuafe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…[30] The lower the binding energy affinity, the more stable conformation, and the higher the binding activity. [31,32] The docking results implied that the key active ingredients exhibited the good binding ability to the four core therapeutic targets (Figure 8A). Meantime, we also found that the results of STAT3, RELA, and MAPK8 are better than AR.…”
Section: Molecular Docking Evaluationmentioning
confidence: 98%
“…[30] The lower the binding energy affinity, the more stable conformation, and the higher the binding activity. [31,32] The docking results implied that the key active ingredients exhibited the good binding ability to the four core therapeutic targets (Figure 8A). Meantime, we also found that the results of STAT3, RELA, and MAPK8 are better than AR.…”
Section: Molecular Docking Evaluationmentioning
confidence: 98%